Monitoring of veterinary drug residues in livestock products with antimicrobial resistance - Dahae Park; Yu Ra Kim; Ji Young Kim; Jang-Duck Choi; Guiim Moon; Dong Woo Shin (Applied Biological Chemistry)
Abstract Antimicrobial resistance (AMR) in animal-derived products remains a global concern, while reports on veterinary drug (VD) residues in such products are relatively rare. This study aimed to investigate the presence of VD residues in livestock products associated with AMR through a preliminary assessment. A total of 28 veterinary drug (VD) residues were identified in the samples, including beef, pork, chicken, and duck, using liquid chromatography-mass spectrometry after extraction. The detected concentrations ranged from 8.0 × 10− 5 mg/kg to 1.564 mg/kg, with anthranilic acid specifically found in all matrices at levels between 0.001 and 1.564 mg/kg. The detection rate was 54.5%, nearly twice as high as that reported in previous national monitoring conducted in South Korea. Moreover, residues such as anthranilic acid and ronidazole exceeded the maximum residue levels (MRLs) established in South Korea, which raises significant concerns. Although the detected VD residues did not align with the specific VDs associated with AMR, the high detection rate and instances of MRL violations underscore the importance of strategic monitoring to ensure the appropriate use of VDs in livestock.